Store Image, Service Quality, and Familiarity on Purchase Intention of Private Label Brand In Indonesia - Surjaatmadja, Surachman; Purnawan, Daruendra (International Review of Management and Marketing, 2018)
This study aims to determine the direct effect of store image and service quality of the brand image and interest in purchasing the private label products. The study also looked at factors that influence directly the interest to buy (purchase intention) consumers. In this study will be the one form of retail which is currently experiencing a significant development that Supercenters industry or other terms that is often used is Hypermarket. This research is classified as descriptive analysis method by taking a sample of a population and the use of a questionnaire as its main tool. The sample of this study is some of200 respondents, especially private label brand customers that live in Indonesia. Respondents were selected using improbability sampling and convenience sampling technique. The results of the analysis using Structural Equation Modelling (SEM) and its result would be summarized as; Store image has significant influence toward a brand imaged purchase intention of private label; Service quality has significant influence toward a brand imaged purchase intention of private label; Brand image has significant influence toward perceived risk and purchase intention of private label; Perceived risk have significant influence over price consciousness and purchase intention of private label; Price consciousness has significant influence toward purchase intention of private label. Perceived Quality has significant influence over purchase intention of private label. Familiarity has significant influence over purchase intention, perceived risk andperceived quality of private label too. Store image has significant influence overperceived quality and perceived risk of private label. Keywords: Store image, service quality, perceived quality, brand image, perceived risk, price consciousness, purchase intention, private labels. JEL Classifications: L8, M31